(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Intramolecular cyclization of 3-(2-carboxyphenyl)- and 3-(2-carboxybenzyl)isocoumarin under the action of strong mineral acids was investigated. The behavior of resulting condensed systems in alkaline medium was studied.